"We are from there, that's our land": contestation, maize, and the problemisation of waste at Blantyre, Malawi's Mzedi dumpsite. Issue 5 (4th May 2022) - Kalina, Marc; Kwangulero, Jonathan; Tilley, Elizabeth
ABSTRACT: Mzedi dumpsite is the only city-run waste facility in the city of Blantyre, Malawi. Although the entire site is city-owned, the periphery of the dumping site has been used for agricultural purposes for generations, but has become a space of contestation between growers, the city, and dump managers, as unregulated dumping has swelled the boundaries of the site, spilling waste into the surrounding fields, accentuating growing pressure for land. Drawing on extensive ethnographic, qualitative fieldwork with growers and other stakeholders within the city of Blantyre, the purpose of this article is to understand and explain the complicated factors and relationships that influence the production of maize on and around the Mzedi dumpsite, while contextualising the motivations that drive growers to cultivate a space that is broadly understood by themselves as hazardous. Building on a previously developed conceptual framework, the investigation utilises a Foucauldian lens to analyse how growers conceptualise and problematise the ways in which Mzedi, and its waste, affects their lives and their crops. Findings suggest that growers' motivations for planting in the vicinity of Mzedi are complex but can broadly attributed to three factors: an historical connection to the land, a lack of other available space, and a belief that the organic waste stored at the dumpsite makes the surrounding land fertile, and suitable for agriculture. These findings contribute towards our understanding of how populations in the Global South conceptualise and problematise "waste".